Missions of Peter I’s Envoys and Savva Lukich Raguzinsky in Istanbul in the Historical and Cultural Aspect - Инанир, Эмине (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The main purpose of the article is to analyse the mission of Peter I’s envoys and Savva Lukich Raguzinsky to Istanbul in the historical and cultural aspect. As commonly known, a significant period in the history of Turkish-Russian relations falls to the end of the 17th century and the first decades of the 18th century. This period coincides with the reforms of Peter the Great in Russia. As a result of the reforms, Russia begins to assimilate European cultural values, but at the same time it continues to show interest in its southern neighbours, namely the Ottoman Empire. In the late 17th century and in the early 18th century, along with the development of political and trade relations between Russia and Turkey, it became increasingly necessary for Peter I to have an experienced diplomat in the Ottoman Empire. The subject of Russian diplomats’ presence in Istanbul, which at that time was a point of encounter of both political interests and religious and cultural traditions of many groups and nations, is studied based on descriptions and reports of Russian ambassadors, the historical work Diplomacy of Peter the Great by N.N. Molchanov, the historical novel by Yuri Fedorov, Russia is Calling for Duty and Nikolai Pavlenko’s historical-fiction Around Throne. Birds of Petro Nest. Passions around the Throne. These works also name persons who assisted the ambassadors in collecting information about the state of the empire. Among these persons, there was a merchant of Serbian origin, Savva Lukich Vladislavich. The activities and entourage of the Russian envoys show the diversity of the ethno-cultural aura of both Istanbul and the Ottoman Empire.